Framework for CSCW applications by using virtual reality - Kubo, Mario Massakuni; Deriggi, Felício V.; Sementille, Antônio Carlos [UNESP]; Brega, José Remo F. [UNESP]; Marques, Daniela; Kirner, Claudio (Institute of Electrical and Electronics Engineers (IEEE), 1999)
This paper discusses aspects of computer supported co-operative work (CSCW) and distributed virtual environments. It presents a framework for CSCW in a distributed virtual environment and an application. The application was developed with WorldToolKit, WorldToWorld tools and the Common Object Request Broker Architecture platform. This application is a useful meeting room of the Virtual Environment for Shared Interactive Visualisation (VESIV) Project, developed by the Virtual Reality Group of the Federal University of Sao Carlos.
Keywords: Computer supported co-operative work and distributed virtual environments